“The EU Charter of Fundamental Rights as an Instrument for Overarching the Lack of Legitimacy of the EU” - Runcheva Tasev, Hristina (Konrad Adenauer Foundation, 2017)
The purpose of this paper is to address the perceived problem of legitimacy of the European Union by shortly explaining the theoretical framework of legitimacy itself and by testing it against the effects of the Charter of Fundamental Rights in the EU. The main research question that is applied is: To what extent does the EU Charter of Fundamental Rights contribute to a more legitimate EU?
Keywords: European Union, legitimacy (input and output legitimacy), Charter of Fundamental Rights